Design and Evaluation of Cross-Cultural Workshops for ESL Teachers and Administrators - McGroarty, Mary. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
Two cross-cultural workshops are outlined and discussed, one designed for graduate students in a training program for teachers of English as a second language and one for public school teachers and administrators. Activities used in each workshop and the rationale for their selection are described in detail. Each workshop included a combination of cognitive, experiential, and affective approaches to cross-cultural topics related to the professional roles of the participants. Evaluation of the workshops was carried out by means of a rating scale and an open-ended questionnaire. The rating scale was a 10-item instrument devised for the goals and content of each workshop and was administered immediately before and after workshop sessions. The questionnaire was distributed after each workshop. The self-rating scale allowed assessment of the effectiveness of the sessions by relating gains in the participants' self-rated awareness of cultural issues to the specific activities chosen for the workshops. To varying degrees, both workshops were perceived as useful by participants, with questionnaire comments corroborating rating scale information. Participants in both workshops made significant gains in self-rated cultural knowledge. Further research into the long-term value of such training in helping educators become more effective in cross-cultural settings at home and abroad is recommended. (Author/MSE)
ERIC Note: Based on a paper presented at the Annual Meeting of the Teachers of English to Speakers of Other Languages (18th, Houston, TX, March 6-11, 1984).
Teachers.
Administrators.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Education; Cross Cultural Training; English (Second Language); Graduate Students; Inservice Teacher Education; Language Teachers; Preservice Teacher Education; Program Design; Program Evaluation; Second Language Instruction; Teacher Education; Workshops; Guides, Classroom -- Teacher; Speeches/Meeting Papers